Who Will Pay? - Heller, Peter S (International Monetary Fund, 2003)
Intro – Contents – Foreword – Acknowledgments – List of Abbreviations – 1 Introduction and Overview – 2 Why Consider Long-Term Issues in Thinking About Fiscal Policy? – 3 How Governments (and Academics) Address Long-Term Issues in Fiscal Policy Planning – 4 Some Conceptual Issues in Addressing Long-Term Fiscal Developments – 5 The Way Forward: Embedding Long-Term Issues in the Fiscal Policy Framework – 6 Summary and Conclusions – Appendix Tables – References – Index – About the Author.
Description based on publisher supplied metadata and other sources
Keywords: Climatic changes; Aging; Fiscal policy; Aging; Economic aspects; Climatic changes; Economic aspects; Electronic books